UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PELAJARAN PPKN BERBASIS ONLINE DI KELAS 1 SMP NEGERI 1 CIRUAS SERANG - Teguh Pujiningsih (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2022)
ABSTRACT This study aims to increase students' learning motivation in PPKN lessons Based online in Class 1 SMP Negeri 1 Ciruas Serang. This research is a classroom action research (classroom action research). The subjects of this study were seventh-grade students at SMP Negeri 1 Ciruas Serang. This study aims to determine the increase in active participation and online-based PPKN learning motivation in seventh-grade students at SMP Negeri 1 Ciruas Serang. This research is a classroom action research (classroom action research). The subjects of this study were students of class VII F at SMP Negeri 1 Ciruas Serang . From the results of the PPKN learning motivation in the pre-action, the average score was 56.63. The number of students who achieved high motivation was 7 students (36.84%), while 12 students (63.16%) had not yet achieved the criteria of low motivation. Based on these results, the researchers and teachers intend to improve and increase the motivation to learn PPKN grade VII students by using online-based PPKN learning. Based on the results of research starting from pre-action, cycle I, to cycle II, it can be explained that students' motivation to learn PPKN online increased after the implementation of PPKN learning using the student discussion method. The increase in online learning motivation can be seen from the average score obtained of 55.55 in the pre-action, increasing to 67.79 in the first cycle and increasing again to 72.5 in the second cycle. rom the description above, it can be concluded that the use of PPKN online learning can increase motivation in class VII students of SMP Negeri 1 Ciruas Serang.